The Competence of Pharmacy Students in Reading Comprehension - Wicaksono, Garda Arif (CV. Tripe Konsultan, 2023)
The puropose of this research were to: 1) investigated the students’ competence in Reading comprehension at pharmacy department, 2) to find out the students’ problems in answer to reading questions. In this research used descriptive quantitative. The research used thirty students at Pharmacy Department at English Course. The data thorugh test. The results of this research show that their competence in reading comprehension was excellent (64%). Most of the students still problems to reading comprehension its show that many students are in fair level or 10 %and very poor level or 12%, its means that still students are less competence to comprehension of reading its cause the students are not understanding means of the questions, lazy for reading which make the students are over answers to avoid the mistake it’s show on results and analysis above. So, it can be conclude that the students at Pharmacy Department Universitas have competence in reading comprehension and the researcher still found that the some of the students are problem to comprehension of reading.